2022
DOI: 10.1007/s10570-022-04647-x
|View full text |Cite
|
Sign up to set email alerts
|

Grafting cellulose nanocrystals with phosphazene-containing compound for simultaneously enhancing the flame retardancy and mechanical properties of polylactic acid

Abstract: Cellulose nanocrystals (CNCs) have been used as bio-based carbon source in intumescent system. However, CNCs have the disadvantages of low onset decomposition temperature and decompose and carbonize during processing. We, herein, demonstrated the design of phosphazenecontaining CNCs (P/N-CNCs) with great thermal stability and outstanding charring ability. The TGA results showed that the initial decomposition temperature of P/N-CNCs was increased from 202.4 ℃ to 272.2 ℃ (increased by 34.5%), and the residual ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Moreover, the LOI result of PLA containing 10% modification with FR cellulose nanofiber reached 25.8% and the UL-94 V-0 grade was achieved. 16 At the same time, He et al 17 reported that the LOI result of PLA with 10 wt% phosphazene-containing cellulose nanocrystals and APP reached 28.1% and the UL-94 V-0 grade was obtained. Wang et al 18 investigated the LOI result of PLA with 30% APP and starch which was found to reach 41.0% and the UL-94 V-0 grade was achieved.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the LOI result of PLA containing 10% modification with FR cellulose nanofiber reached 25.8% and the UL-94 V-0 grade was achieved. 16 At the same time, He et al 17 reported that the LOI result of PLA with 10 wt% phosphazene-containing cellulose nanocrystals and APP reached 28.1% and the UL-94 V-0 grade was obtained. Wang et al 18 investigated the LOI result of PLA with 30% APP and starch which was found to reach 41.0% and the UL-94 V-0 grade was achieved.…”
mentioning
confidence: 95%
“…Recently, sustainable biological FR additives, such as lignin, [10][11][12][13][14] cellulose, [15][16][17] starch, 18,19 chitosan (CS), [20][21][22][23] protein, 24 b-cyclodextrin (CD), 25,26 polydopamine (PDA), 29 phytic acid (PA), [30][31][32][33] vegetable oils, furan (FA) [35][36][37] etc. have become a hot and attractive topic.…”
mentioning
confidence: 99%
“…33,34 Therefore, surface modification of CNCs is widely adopted to enhance the hydrophobicity thus the dispersion state of CNCs in polymer matrix would be significantly improved. [35][36][37][38][39] In this study, electrospun stereocomplex PLA fibers (Sc-fibers) and PLLA grafted cellulose nanocrystals (g-CNCs) were prepared as nano-fillers and then blended with PLLA matrix to investigate the crystallization and mechanical properties of PLLA. For comparison, a PLLA nanocomposite containing Sc-fibers and g-CNCs, respectively was also prepared.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 The dense char layer formed by the condensed phase reaction is primarily responsible for its effect. [35][36][37][38][39][40][41] For example, in epoxy resin, APP and activated carbon-supported Fe 2 O 3 inhibited decomposition and promoted the formation of a stable char layer, effectively improving the flame retardancy of the matrix. 42 Hydroxide flame retardant additives such as aluminum hydroxide (ATH), magnesium hydroxide (MH), and layered double hydroxides (LDHs) are inexpensive, nontoxic, smoke-free, and halogen-free.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, APP is used as an effective intumescent flame retardant in a variety of polymers 33,34 . The dense char layer formed by the condensed phase reaction is primarily responsible for its effect 35–41 . For example, in epoxy resin, APP and activated carbon‐supported Fe 2 O 3 inhibited decomposition and promoted the formation of a stable char layer, effectively improving the flame retardancy of the matrix 42 …”
Section: Introductionmentioning
confidence: 99%